Combined effects of temperature and copper on oxygen consumption and antioxidant responses in the mudflat fiddler crab Minuca rapax (Brachyura, Ocypodidae) - Capparelli, Mariana Vellosa; Bordon, Isabella C. [UNESP]; Araujo, Giuliana [UNESP]; Gusso-Choueri, Paloma Kachel [UNESP]; Souza Abessa, Denis Moledo de [UNESP]; McNamara, John Campbell (Elsevier B.V., 2019)
This study investigates the combined effects of waterborne copper exposure and acute temperature change on oxygen consumption and the oxidative stress biomarkers, glutathione S-transferase (GST) and glutathione peroxidase (GPx), in the gills and hepatopancreas of the fiddler crab Minuca rapax. Crabs held at 25 degrees C were acclimated to 0 (control), 50, 250 or 500 mu g Cu L-1 for 21 days, and were then subjected to 15, 25 and 35 degrees C for 24 h. Aerial oxygen consumption rates of crabs in copper free media increased with increasing temperature from 15 to 35 degrees C, Q(10) values reaching approximate to 3. Crabs exposed to increasing copper concentrations exhibited variable responses, Q so values falling to approximate to 1.5. Copper had no effect on oxygen consumption at 25 degrees C. However, at 35 degrees C, rates decreased in a clear concentration-response manner in the copper exposed crabs, revealing impaired aerobic capability. At 15 degrees C, oxygen consumption rates increased with copper concentration, except, for a decrease at 500 mu g CuL-1. Gill GST activity was approximate to 2-fold that of the hepatopancreas, while hepatopancreas GPx activity was 3-fold that of the gills. Gill GST activities were reduced by copper exposure only at 25 degrees C while hepatopancreas GST activities were altered by copper at all temperatures. Hepatopancreas GST and GPx activities increased in crabs exposed to copper at 35 degrees C, revealing oxidative stress induction. Hepatopancreas GST and GPx activities were reduced in copper exposed crabs at 15 degrees C, suggesting a diminished capability to mitigate the effects of copper exposure at low temperature. These findings reveal that copper exposure increases oxygen consumption at low temperatures but decreases consumption at high temperature. Hepatopancreas GPx activities decreased at low temperature and increased at high temperature. These novel findings demonstrate that the interaction between copper exposure and temperature should be considered when evaluating biomarker activities in semi-terrestrial crabs.
Keywords: Oxygen consumption; Anti-oxidant activities; Biomarkers; Copper exposure; Temperature effects; Gelasiminae; Semi-terrestrial fiddler crab